EFFORTS TO IMPROVE PIK R MANAGEMENT THROUGH GENRE PROGRAM TRAINING FOR FAMILY PLANNING EXTENDER - Anwar, Syaeful; Rukanda, Nandang (IKIP Siliwangi Bandung, 2025)
This research is motivated by data that states that PIK R managers must get updated information regarding good and correct PIK R management, this update was carried out because BKKBN had not provided a briefing activity for PIK R managers. In addition, the cadre has always been running as long as natural with the number of registered participants 3,053 as active participants so far and updated information. The theory used in this research is the theory of training, the theory of PIK R, and the theory of Family Planning Extension. The method used is a qualitative method with a qualitative descriptive approach. Data collection techniques using interviews and observation. The research location is at the BKKBN Representative for West Java Province, Jalan Surapati No. 122, Cihaur Geulis, Cibeunying Kaler District, Bandung City. A sample of one training implementer and three representatives of training participants were selected randomly.Based on the results and discussion that training can improve the ability and understanding of family planning instructors to be able to update the management of information, services, and counseling for adolescents in West Java, especially PIK R. realizing teenagers who have a family life plan and will be ready to build a happy and prosperous family.